Enhanced Kinetics over VS4 Microspheres with Multidimensional Na+ Transfer Channels for High‐Rate Na‐Ion Battery Anodes. Issue 23 (18th November 2019) - Li, Wenbin; Huang, Jianfeng; Li, Ruizi; Cao, Liyun; Li, Xifei; Chen, Shaoyi; Feng, Liangliang
Abstract: Developing 3 D self‐assembled nanoarchitectures with well‐defined crystal structures is an effective strategy to enhance the electrochemical performances of electrode materials. (1 1 0)‐oriented and bridged‐nanoblocks self‐assembled VS4 microspheres are controllably synthesized by a facile one‐step hydrothermal method. The (1 1 0)‐bridged structure sets up open pathways for Na + diffusion among nanoblocks, and the (1 1 0)‐oriented structure provides unobstructed pathways for Na + diffusion in the nanoblocks, which collectively constructs multidimensional Na + transfer channels in the VS4 microspheres, promoting the electrochemical kinetics. As an anode for Na‐ion batteries (SIBs), this material exhibits pseudocapacitive Na + storage and excellent rate capability, delivering high capacities of 339 and 270 mAh g −1 at rates of 0.1 and 2.0 A g −1, respectively, with a capacity retention of 79 % in the voltage window of 0.5–3.0 V. In particular, the reversible capacity reaches 575 mAh g −1 after 300 cycles even at 1.0 A g −1 in the voltage window of 0.05–3.0 V, outperforming those of the ever‐reported VS4 ‐based anode materials. This work presents an effective strategy to the exploration and design of high‐performance anodes for SIBs. Abstract : Ordered channels, improved performance : Ordered and bridged nanoblocks‐self‐assembled VS4 microspheres are prepared through a facile one‐step hydrothermal method. The synergistic effect of (1 1 0)‐oriented and bridged structures that collectively construct multidimensional Na + transfer channels in the VS4 microspheres leads to an electrode that shows dramatically enhanced rate capability when used in Na‐ion batteries.